Vehicle interior materials
Patent Information
- Application Number
- JP2021108092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-29
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-06-29
Smart Images

Figure 0007651392000001 
Figure 0007651392000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an interior material for a vehicle. [Background technology]
[0002] Background Art Expanded bead molded articles (hereinafter also referred to as expanded bead molded articles or molded articles) using a composite resin containing an ethylene-based resin component and a styrene-based resin component as a base resin have excellent rigidity, resilience, cushioning properties, etc., and are therefore used as packaging materials for precision parts and heavy products, and interior materials for vehicles such as deck boards, tool boxes, bumpers, and floor spacers.
[0003] Such a molded article is produced, for example, by using expandable composite resin particles as follows. First, the composite resin particles are impregnated with an organic physical blowing agent such as butane or pentane to produce expandable composite resin particles. Next, the expandable composite resin particles are heated with steam or the like to expand the expandable composite resin particles to obtain expanded particles. Next, the expanded particles are expanded in a mold by in-mold molding, and the expanded particles are fused to each other. In this manner, a molded article can be obtained.
[0004] On the other hand, since the molded article obtained as described above is flammable, techniques for imparting flame retardancy to the molded article have been developed. For example, Patent Document 1 proposes expandable composite resin particles containing a brominated styrene-butadiene copolymer as a flame retardant. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-180038 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, there has been a demand for increasing the expansion ratio of expanded bead moldings used in vehicle interior materials to reduce their weight. However, in the case of expanded bead moldings formed using expandable composite resin particles containing an organic physical foaming agent, if the expansion ratio of the expanded bead molding is increased to reduce the weight, there is a risk that the expanded bead molding will become more flammable. In addition, depending on the shape of the vehicle interior material, the molding may have a thin-walled part that is thinner than the surrounding area, and such a thin-walled part tends to be more flammable than a thick part. Therefore, when the molding has a thin-walled part, increasing the expansion ratio may make the molding more flammable.
[0007] In addition, foamed bead moldings used as vehicle interior materials are required to be lightweight and flame retardant, to emit less volatile organic compounds such as unreacted styrene monomers, and to have excellent bending rigidity. However, conventional foamed bead moldings still have room for improvement in terms of improving these physical properties in a well-balanced manner.
[0008] The present invention has been made in view of the above background, and aims to provide a vehicle interior material which is lightweight, emits little styrene-based monomer, and has high bending rigidity and excellent flame retardancy. [Means for solving the problem]
[0009] One aspect of the present invention is a vehicle interior material made of an expanded bead molding, the foamed bead molding has a base resin that is a composite resin obtained by impregnating and polymerizing an ethylene-based resin with a styrene-based monomer, and contains a flame retardant mainly composed of a brominated bisphenol-based flame retardant; the organic physical blowing agent remains in the expanded bead molding, The content of xylene insoluble matter in the composite resin is 5% by mass or more and 20% by mass or less, The apparent density of the expanded bead molding is 15 kg / m 3 More than 40kg / m 3 is as follows: the breaking strain of the expanded bead molding is 20% or more and the bending modulus of the expanded bead molding is 20 MPa or more, as measured in accordance with JIS K 7221-2:2006; The content of a styrene-based monomer in the expanded bead molding is 0 ppm by mass or more and 50 ppm by mass or less, The vehicle interior material satisfies one of the following conditions when subjected to a flammability test based on FMVSS No. 302: (1) the foamed bead molding exhibits self-extinguishing properties, and (2) the burning rate of the foamed bead molding is 60 mm / min or less. Effect of the Invention
[0010] The vehicle interior material is made of the specific foamed bead molding containing a composite resin as a base resin and a brominated bisphenol-based flame retardant. The vehicle interior material made of the foamed bead molding is lightweight, emits little styrene monomer, and has high bending rigidity and excellent flame retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Next, preferred embodiments of the vehicle interior material and the foamed bead molding constituting the vehicle interior material will be described. In this specification, when "~" is used with a numerical value or a physical property value between the two, the values before and after the "~" are included. In addition, parts by mass and parts by weight have substantially the same meaning, % by mass and % by weight have substantially the same meaning, and ppm by mass and ppm by weight have substantially the same meaning.
[0012] The vehicle interior material is used in vehicles such as automobiles and railroad cars. More specifically, the vehicle interior material may be configured as an automobile interior material such as an in-vehicle container such as a toolbox or luggage box in an automobile, a floor material such as a floor spacer or tibia pad, a door trim, a headliner, an armrest, various pillars, a seat back, a headrest, a seat raising material, a side impact pad, a console box, a console lid, a partition board, a trunk lid, etc. The vehicle interior material may also be configured as a railroad car interior material such as a door, a seat, or a ceiling member in a railroad car.
[0013] The vehicle interior material is composed of an expanded bead molded body (hereinafter also referred to as "molded body" as appropriate) obtained by molding expanded beads in a mold. For example, the vehicle interior material may be an expanded bead molded body molded into a desired shape by in-mold molding. The vehicle interior material may also be an expanded bead molded body molded into a desired shape by cutting or the like after in-mold molding is completed. Furthermore, the vehicle interior material may be formed by subjecting the expanded bead molded body to necessary processing, decoration, and the like, as necessary, as needed.
[0014] The expanded bead molding uses a composite resin as a base resin, which is obtained by impregnating and polymerizing an ethylene-based resin with a styrene-based monomer. That is, the composite resin contains a component derived from the ethylene-based resin and a component derived from the styrene-based monomer. For the ethylene-based resin and the styrene-based monomer, the explanation of the ethylene-based resin and the styrene-based monomer in the expandable composite resin particles (hereinafter, appropriately referred to as "expandable particles") described later can be appropriately referred to.
[0015] The expanded beads constituting the expanded bead molding are obtained by expanding expandable composite resin beads containing a flame retardant mainly composed of a brominated bisphenol flame retardant and an organic physical blowing agent. The more detailed configurations of the expanded beads and the expandable beads will be described later. The expanded beads obtained by expanding the expandable beads are sometimes called "composite resin expanded beads."
[0016] The mass ratio of the component derived from the ethylene resin and the component derived from the styrene monomer in the molded product is preferably 50:50 to 5:95 (component derived from the ethylene resin:component derived from the styrene monomer). In this case, the ratio of the ethylene resin component and the styrene resin component is good, and the molded product can be easily made lighter and exhibits excellent rigidity and toughness in a stable manner. From the viewpoint of facilitating the production of a molded product with increased rigidity, the mass ratio of the component derived from the ethylene resin and the component derived from the styrene monomer is preferably 20:80 to 5:95 (component derived from the ethylene resin:component derived from the styrene monomer). From the viewpoint of enhancing the rigidity and toughness of the molded body in a well-balanced manner, the mass ratio of the component derived from the ethylene-based resin to the component derived from the styrene-based monomer (component derived from the ethylene-based resin:component derived from the styrene-based monomer) is preferably 40:60 to 6:94, more preferably 30:70 to 8:92, even more preferably 20:80 to 10:90, and particularly preferably 18:82 to 10:90.
[0017] The base resin of the molded body, that is, the composite resin, contains a flame retardant mainly composed of a brominated bisphenol flame retardant. Examples of the brominated bisphenol flame retardant include bisphenol A, bisphenol F, bisphenol S, or brominated derivatives thereof. More specifically, brominated bisphenol A flame retardants such as 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane and 2,2-bis(4-(2,3-dibromopropoxy)-3,5-dibromophenyl)propane, and brominated bisphenol S flame retardants such as bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone are used. These brominated bisphenol flame retardants may be used alone or in combination of two or more.
[0018] In the expanded bead molding, the brominated bisphenol flame retardant is the main component of the flame retardant, that is, the component with the largest amount of the flame retardant contained in the expanded bead molding. The proportion of the brominated bisphenol flame retardant in the flame retardant is preferably 50% by mass or more relative to 100% by mass of the total amount of the flame retardant. In this case, excellent flame retardancy can be stably imparted to the molded body. From the viewpoint of more reliably obtaining such an effect, the proportion of the brominated bisphenol flame retardant in the flame retardant is preferably 60% by mass or more relative to 100% by mass of the total amount of the flame retardant, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and particularly preferably 100% by mass, that is, the flame retardant is composed only of the brominated bisphenol flame retardant.
[0019] In addition, the brominated bisphenol flame retardant contained in the expanded bead molding is preferably a brominated bisphenol A flame retardant. The brominated bisphenol A flame retardant can impart excellent flame retardancy to the molding even when the amount of the brominated bisphenol A flame retardant is relatively small. From the same viewpoint, the brominated bisphenol flame retardant is preferably a compound having a 2,3-dibromo-2-methylpropyl group and / or a 2,3-dibromopropyl group. In addition, the brominated bisphenol flame retardant is more preferably 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane. For the brominated bisphenol flame retardant, the explanation of the brominated bisphenol flame retardant in the expandable beads described later can be appropriately referred to.
[0020] The amount of the brominated bisphenol flame retardant in the molded body is preferably 0.1 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the composite resin. In this case, the molded body can be stably imparted with flame retardancy while maintaining the rigidity and toughness of the molded body. From the viewpoint of stably increasing the flame retardancy of the molded body, the amount of the brominated bisphenol flame retardant is preferably 0.5 parts by mass or more relative to 100 parts by mass of the composite resin, more preferably 1.0 parts by mass or more, even more preferably 1.2 parts by mass or more, and particularly preferably 1.5 parts by mass or more. In addition, from the viewpoint of stably increasing the rigidity and toughness of the molded body, the amount of the brominated bisphenol flame retardant is preferably 2.8 parts by mass or less relative to 100 parts by mass of the composite resin, more preferably 2.5 parts by mass or less, even more preferably 2.2 parts by mass or less, and particularly preferably 1.8 parts by mass or less.
[0021] The base resin may contain a flame retardant other than the brominated bisphenol flame retardant, but the base resin preferably does not substantially contain a brominated styrene-butadiene copolymer as a flame retardant. More specifically, the proportion of the brominated styrene-butadiene copolymer in the flame retardant is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, relative to the total amount of the flame retardant blended (100% by mass), and is particularly preferably 0% by mass, i.e., the base resin does not contain a brominated styrene-butadiene copolymer.
[0022] The molded product preferably contains a radical generator having a 10-hour half-life temperature of 150° C. or more as a flame retardant auxiliary. In this case, the flame retardancy can be further improved while suppressing the decrease in toughness of the molded product. For the flame retardant auxiliary, the explanation of the flame retardant auxiliary in the expandable particles described later can be appropriately referred to. When the molded product contains a flame retardant auxiliary, from the viewpoint of stably increasing the flame retardancy of the molded product while maintaining the bending strength of the molded product, the mass ratio of the flame retardant auxiliary to the flame retardant is preferably 0.1 to 1, more preferably 0.12 to 0.6, and even more preferably 0.15 to 0.5. From the same viewpoint, the blending amount of the flame retardant auxiliary is preferably 0.1 to 1 part by mass, more preferably 0.2 to 0.5 parts by mass, and even more preferably 0.3 to 0.4 parts by mass relative to 100 parts by mass of the composite resin.
[0023] The glass transition temperature of the methyl ethyl ketone soluble content in the composite resin in the molded product is preferably 102°C or higher, more preferably 103°C or higher, and even more preferably 105°C or higher. In this case, the mechanical properties of the molded product in a high-temperature environment can be improved. On the other hand, the upper limit of the glass transition temperature of the methyl ethyl ketone soluble content in the composite resin is not particularly limited as long as it is within a range that does not impair the above-mentioned action and effect, but may be approximately 115°C, 110°C, or 108°C. The methyl ethyl ketone soluble content in the composite resin is mainly a styrene-based resin component. The glass transition temperature of the methyl ethyl ketone soluble content can be adjusted by the component derived from the styrene-based monomer that constitutes the styrene-based resin component.
[0024] The glass transition temperature of the methyl ethyl ketone soluble matter is measured, for example, as follows. First, a test piece cut out from the expanded bead molding is immersed in methyl ethyl ketone at a temperature of 23° C. for a predetermined time. Next, the methyl ethyl ketone solution in which the methyl ethyl ketone soluble matter is dissolved is collected. By dropping this methyl ethyl ketone solution into methanol, the white methyl ethyl ketone soluble matter is precipitated in the methanol. The methyl ethyl ketone soluble matter is recovered from the methanol and then thoroughly dried.
[0025] 2-4 mg of the methyl ethyl ketone soluble matter thus obtained is used as a sample, and a heat flux differential scanning calorimeter (DSC) DSC250 manufactured by TA Instruments is used to perform heat flux differential scanning calorimetry based on JIS K 7121-1987. Specifically, the condition of the sample is adjusted based on "(3) When measuring the glass transition temperature after a certain heat treatment" specified in JIS K 7121-1987, and then a DSC curve is obtained under the condition of a heating rate of 20°C / min. The midpoint glass transition temperature of this DSC curve is taken as the glass transition temperature of the methyl ethyl ketone soluble matter.
[0026] The mass ratio of the xylene insoluble matter in the composite resin in the molded body is 5% by mass or more and 20% by mass or less. The xylene insoluble matter in the composite resin is mainly a crosslinked ethylene-based resin component. By setting the mass ratio of the xylene insoluble matter in the composite resin within the specific range, the expandability of the expandable particles and the moldability of the expanded particles are improved, and a lightweight molded body can be obtained. In addition, by setting the mass ratio of the xylene insoluble matter in the composite resin within the specific range, the flame retardancy of the molded body is increased, and even if the molded body has a thin-walled portion, the molded body can be made less flammable.
[0027] The mass ratio of the xylene insoluble matter in the composite resin is preferably 6% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more. In this case, excellent flame retardancy can be more stably imparted to the molded body. In addition, the mass ratio of the xylene insoluble matter in the composite resin is more preferably 18% by mass or less, even more preferably 16% by mass or less, and particularly preferably 15% by mass or less. In this case, the molded body can be more easily lightened. In addition, in this case, the fusion state between the expanded particles constituting the molded body can be stably and satisfactorily maintained. The xylene insoluble matter in the composite resin in the molded body is a solid (insoluble matter) obtained after extracting the xylene soluble matter from the molded body by Soxhlet extraction using xylene as a solvent.
[0028] Furthermore, the weight average molecular weight of the styrene-based resin component in the composite resin in the molded product is preferably 150,000 to 400,000, more preferably 180,000 to 350,000, and even more preferably 200,000 to 300,000. In this case, the variation in bending properties of the molded product can be reduced, and molded products having excellent bending properties can be stably obtained.
[0029] The molded article may contain an organic physical foaming agent within a range that does not impair the effects of the present invention. For example, the content of the organic physical foaming agent in the molded article is preferably 3% by mass or less, more preferably 2.5% by mass or less, and even more preferably 2.2% by mass or less. In this case, the flame retardancy of the molded article can be further improved.
[0030] From the viewpoint of improving the flame retardancy of the molded body, there is no lower limit to the content of the organic physical foaming agent in the molded body, but in the manufacturing method of the molded body, the organic physical foaming agent contained in the expandable composite resin particles described later usually remains in the expanded particles or the molded body. That is, the expanded particle molded body constituting the interior material for a vehicle usually contains an organic physical foaming agent. From this viewpoint, the lower limit of the content of the organic physical foaming agent in the molded body may be, for example, 0.01% by mass, 0.05% by mass, or 0.1% by mass. In the molded body, by adjusting the amount of the flame retardant, for example, even when the content of the organic physical foaming agent in the molded body is 1% by mass or more, the molded body can be given flame retardancy.
[0031] As described above, in the molded product after molding in the mold, a part of the organic physical foaming agent contained in the expandable particles usually remains in the molded product, but the content of the organic physical foaming agent in the molded product can be reduced by dissipating the organic physical foaming agent from the molded product. As a method for dissipating the organic physical foaming agent from the molded product, there is a method of leaving the molded product to stand for 1 to 4 days, for example, in an environment at a temperature of 20 to 80°C to cure it.
[0032] The organic physical blowing agent is preferably a saturated hydrocarbon having a carbon number of 3 to 6. For the organic physical blowing agent, the description of the organic physical blowing agent in the expandable particles described later can be appropriately referred to.
[0033] The apparent density of the molded body is 15 kg / m 3 More than 40kg / m 3 When the apparent density is in the above range, the molded product is lightweight and has excellent bending properties such as rigidity. From the viewpoint of further improving bending properties such as rigidity, the apparent density of the molded product is 18 kg / m or less. 3 It is preferable that the density is 20 kg / m or more. 3 More preferably, it is 25 kg / m or more. 3 On the other hand, from the viewpoint of further improving the light weight, the apparent density of the molded body is 38 kg / m 3 It is preferable that the thickness is less than 35 kg / m 3More preferably, it is 33 kg / m or less. 3 It is even more preferable that:
[0034] The molded product may contain unreacted styrene monomer remaining in the manufacturing process. For example, when a flame retardant is added during polymerization of composite resin particles in order to impart flame retardancy to the molded product, the polymerization of the styrene monomer is likely to be inhibited, and the amount of unreacted styrene monomer remaining in the composite resin particles may increase. In the conventional technology, when a molded product is manufactured using such composite resin particles, the amount of styrene monomer in the molded product increases, which may lead to an increase in the content of VOC (volatile organic compounds), an increase in the amount of styrene monomer emitted into the interior of a car, and a decrease in flame retardancy.
[0035] In contrast, by producing a molded body using expandable particles with a reduced content of styrene-based monomer, the content of the styrene-based monomer in the molded body can be reduced while imparting flame retardancy to the molded body. Methods for reducing the content of the styrene-based monomer in the expandable particles include, for example, a method for reducing the amount of unreacted styrene monomer remaining in the composite resin particles after polymerization by using a specific polymerization initiator, and a method for reducing the content of the styrene-based monomer by performing a stripping treatment on the composite resin particles. These methods may be performed alone or in combination of two or more methods. The stripping treatment is an operation in which the composite resin particles are heated in an aqueous medium to extract and remove the VOC components (specifically, the unreacted styrene-based monomer) in the composite resin together with the evaporated water. Details of the stripping treatment will be described later.
[0036] The content of the styrene-based monomer in the molded product is preferably 0 ppm by mass or more and 50 ppm by mass or less, more preferably 0 ppm by mass or more and less than 30 ppm by mass, even more preferably 0 ppm by mass or more and 25 ppm by mass or less, and particularly preferably 0 ppm by mass or more and 20 ppm by mass or less. In this case, the content of VOC (volatile organic compounds) is low, and the emission of the styrene-based monomer into the interior of a car or the like can be suppressed, and a molded product having better flame retardancy can be obtained. Such a molded product is suitable for use as a vehicle interior material. From the viewpoint of suppressing the emission of the styrene-based monomer into the interior of a car or the like, the content of the styrene-based monomer in the molded product is most preferably 0 ppm by mass, but due to the manufacturing method of the molded product, the styrene-based monomer may remain in the molded product. From this viewpoint, the content of the styrene-based monomer in the molded product may be 5 ppm by mass or more, or may be 10 ppm by mass or more.
[0037] The molded article has a breaking strain of 20% or more and a flexural modulus of 20 MPa or more, as measured according to JIS K 7221-2:2006. The breaking strain and flexural modulus of the molded article being within the above ranges means that the foamed particles are well fused together and that the molded article has excellent toughness and flexural rigidity. Therefore, a molded article having such physical properties is unlikely to break or bend when loaded with cargo or when a large load is applied, and is therefore suitable as a vehicle interior material.
[0038] From the viewpoint of further improving the toughness of the molded body, the breaking strain of the molded body is preferably 21% or more, more preferably 22% or more. In addition, the breaking strain of the molded body is 20% or more even when the molded body does not break in a bending test based on JIS K 7221-2:2006. On the other hand, from the viewpoint of the toughness of the molded body, the upper limit of the breaking strain is not particularly limited, but the upper limit of the breaking strain is preferably about 30%.
[0039] From the viewpoint of further improving the bending rigidity of the molded article, the bending elastic modulus of the molded article is preferably 21 MPa or more, more preferably 22 MPa or more. On the other hand, from the viewpoint of the bending rigidity of the molded article, the upper limit of the bending elastic modulus of the molded article is not particularly limited, but the upper limit of the breaking strain may be, for example, about 30 MPa, 28 MPa, or 26 MPa.
[0040] The foamed bead molding has characteristics that satisfy either one of the following conditions (1) and (2) in a flammability test based on Federal Motor Vehicle Safety Standards (FMVSS) No. 302. Condition (1): The foamed bead molding exhibits self-extinguishing properties. Condition (2): The combustion rate of the expanded bead molding is 60 mm / min or less.
[0041] In addition, the phrase "the expanded bead molding exhibits self-extinguishing properties" in condition (1) means that any one of conditions (1a) to (1c) is satisfied: condition (1a) the expanded bead molding does not ignite; condition (1b) the combustion of the expanded bead molding ends before it reaches the position where the combustion time measurement is started; and condition (1c) the combustion of the expanded bead molding ends within 60 seconds after it reaches the position where the combustion time measurement is started, and the combustion distance from the position where the combustion time measurement is started to the position where the combustion ends is within 51 mm.
[0042] The molded article having the above-mentioned characteristics has excellent flame retardancy conforming to the FMVSS No. 302 standard, and can therefore be suitably used as an interior material for vehicles. From the viewpoint of further enhancing the flame retardancy of the molded article, it is preferable that the molded article has a characteristic that satisfies any one of the above conditions (1) and (3): the burning rate of the expanded bead molding is 40 mm / min or less, it is more preferable that the molded article has a characteristic that satisfies any one of the above conditions (1) and (4): the burning rate of the expanded bead molding is 20 mm / min or less, and it is even more preferable that the molded article has a characteristic that satisfies the above condition (1) (i.e., the expanded bead molding exhibits self-extinguishing properties).
[0043] In the case of producing a molded body using expandable particles containing an organic physical foaming agent, a method is conceivable for reducing the weight of the molded body while maintaining its rigidity by increasing the ratio of the styrene-based resin component in the composite resin and increasing the expansion ratio of the molded body. However, when such a method is adopted in the conventional technology, the molded body tends to be easily burned due to the components in the composite resin, the organic physical foaming agent remaining in the molded body, the high expansion ratio, etc. In particular, in the case of vehicle interior material applications, the molded body may have a thin part (thin part) with a minimum thickness of less than 10 mm, but such a thin part is more easily burned than a thick part, so this tendency is more pronounced. In addition, even if a flame retardant is blended into the molded body to make it less flammable, there are cases where the desired flame retardant performance cannot be imparted, and blending a flame retardant into the molded body may reduce the rigidity and toughness of the molded body.
[0044] In contrast, in the present invention, a composite resin having a xylene insoluble content within a specific range is used as the base resin, and a bisphenol-based flame retardant is used as the flame retardant, so that a molded product that satisfies the flexural modulus, the flexural break strain, and the FMVSS No. 302 standard can be obtained.
[0045] The foamed bead molding constituting the vehicle interior material can be obtained, for example, by foaming composite resin foamed beads obtained by foaming expandable composite resin beads in a mold. Preferred embodiments of the expandable composite resin beads and the composite resin foamed beads used to form the foamed bead molding will be described below.
[0046] The expandable composite resin particles have a composite resin as a base resin, which is obtained by impregnating and polymerizing an ethylene-based resin with a styrene-based monomer. Such a composite resin contains at least an ethylene-based resin component derived from an ethylene-based resin and a styrene-based resin component derived from a styrene-based monomer. In other words, the expandable particles have a composite resin as a base resin, which contains an ethylene-based resin component and a styrene-based resin component, and the base resin contains a blowing agent and a flame retardant.
[0047] The composite resin foamed beads are particulate foams that use a composite resin obtained by impregnating and polymerizing an ethylene resin with a styrene monomer as a base resin and that contain a flame retardant in the base resin. The foamed beads are composed of a composite resin that contains at least an ethylene resin component and a styrene resin component, and have a structure that contains a large number of bubbles. The foamed beads are obtained, for example, by expanding the above-mentioned expandable beads.
[0048] The expanded beads are used, for example, to produce a molded article by expanding the expanded beads in a mold and fusing the expanded beads to each other. Such a molded article is formed by fusing a large number of expanded beads to each other.
[0049] Since the expandable particles and the expanded particles have a composite resin of an ethylene-based resin component and a styrene-based resin component as the base resin as described above, the molded article has both the properties of an ethylene-based resin and the properties of a styrene-based resin. Specifically, by sufficiently fusing the expanded particles, the molded article can have both excellent toughness and excellent rigidity.
[0050] In the expandable particles and the expanded particles, the mass ratio of the component derived from the ethylene resin and the component derived from the styrene monomer is preferably 50:50 to 5:95 (component derived from the ethylene resin:component derived from the styrene monomer). In this case, the retention of the blowing agent in the expandable particles can be further improved, so that even when the expandable particles are transported and stored, the expandability can be maintained for a long period of time. In addition, since such expandable particles have excellent expandability, they can be expanded at a high ratio. Furthermore, the molded article obtained by using such expandable particles is lightweight and exhibits excellent rigidity and toughness. From the viewpoint of easily obtaining a molded article with higher rigidity, the mass ratio of the component derived from the ethylene resin and the component derived from the styrene monomer is preferably 20:80 to 5:95 (component derived from the ethylene resin:component derived from the styrene monomer). From the viewpoint of enhancing the rigidity and toughness of the molded body in a well-balanced manner, the mass ratio of the component derived from the ethylene-based resin to the component derived from the styrene-based monomer (component derived from the ethylene-based resin:component derived from the styrene-based monomer) is preferably 40:60 to 6:94, more preferably 30:70 to 8:92, even more preferably 20:80 to 10:90, and particularly preferably 18:82 to 10:90.
[0051] As the ethylene-based resin component, for example, linear low-density polyethylene, branched low-density polyethylene, high-density polyethylene, ethylene-acrylic acid copolymer, ethylene-acrylic acid alkyl ester copolymer, ethylene-methacrylic acid alkyl ester copolymer, ethylene-vinyl acetate copolymer, or a mixture of two or more of these can be used. Among these, it is preferable to use at least linear low-density polyethylene as the ethylene-based resin. In this case, the molded article has better toughness. The linear low-density polyethylene is a copolymer of ethylene and an α-olefin such as 1-butene or 1-hexene, and has a density of about 0.910 g / cm. 3 More than 0.930g / cm 3 means something less than.
[0052] The content of linear low density polyethylene in 100% by mass of ethylene-based resin is preferably 50% by mass or more from the viewpoint of improving the toughness of the molded article. From the above viewpoint, the content of linear low density polyethylene is more preferably 70% by mass or more, and even more preferably 80% by mass or more, and it is even more preferable that the ethylene-based resin is substantially composed of linear low density polyethylene. Note that, "the ethylene-based resin is substantially composed of linear low density polyethylene" means that the content of linear low density polyethylene is more than 95% by mass. From the viewpoint of further increasing the strength of the molded article against bending deformation, the content of vinyl acetate component in the composite resin is preferably less than 0.2% by mass, and more preferably 0% by mass, that is, no vinyl acetate component is contained in the composite resin.
[0053] Among linear low density polyethylenes, linear low density polyethylenes polymerized using a metallocene polymerization catalyst are more preferred. In this case, the toughness of the molded article is further improved. In addition, in this case, the amount of low molecular weight components contained in the expandable particles is reduced, and the fusion strength between the expanded particles of the molded article can be further increased, making it possible to produce a molded article that is less susceptible to cracking. Furthermore, a molded article can be obtained that combines the excellent rigidity of a styrene-based resin and the excellent toughness of an ethylene-based resin at a higher level.
[0054] From the viewpoint of foaming property, the melt mass flow rate (MFR 190°C, load 2.16 kg) of the ethylene resin is preferably 0.5 to 4.0 g / 10 min, more preferably 1.0 to 3.0 g / 10 min. The MFR (190°C, load 2.16 kg) of the ethylene resin is a value measured under condition code D based on JIS K7210:1999. As a measuring device, a melt indexer (for example, Model L203 manufactured by Takara Kogyo Co., Ltd.) can be used.
[0055] The melting point (Tm) of the ethylene-based resin is preferably 80°C to 115°C. In this case, the ethylene-based resin can be sufficiently impregnated with the styrene-based monomer during the production of the expandable particles, and the suspension system can be prevented from becoming unstable during polymerization. As a result, by using the expandable particles, it is possible to obtain a molded product having both the excellent rigidity of the styrene-based resin and the excellent toughness of the ethylene-based resin at a higher level. From the same viewpoint, the melting point (Tm) of the ethylene-based resin is more preferably 85°C to 110°C. The melting point (Tm) of the ethylene-based resin can be measured by differential scanning calorimetry (DSC) based on JIS K7121:1987.
[0056] As described above, the composite resin is a resin obtained by impregnating and polymerizing an ethylene-based resin with a styrene-based monomer, and is a resin containing a component derived from an ethylene-based resin and a component derived from a styrene-based monomer. Note that the main component of the component derived from the styrene-based monomer is a styrene-based resin obtained by polymerizing the styrene-based monomer. The composite resin is a concept different from a mixed resin obtained by melt-kneading a polymerized ethylene-based resin and a polymerized styrene-based resin. In this specification, styrene and a monomer copolymerizable with styrene are referred to as a styrene-based monomer. As the styrene-based monomer, styrene may be used alone, or a monomer copolymerizable with styrene may be used in combination with styrene. The styrene-based monomer will be described later.
[0057] Examples of the styrene-based resin component include polystyrene and copolymers containing at least a structural unit derived from styrene. Specific examples include polystyrene, rubber-modified polystyrene, acrylonitrile-butadiene-styrene resin, acrylonitrile-styrene resin, acrylonitrile-ethylene-styrene resin, and mixtures of two or more of these. Among these, preferred are polystyrene and copolymers of styrene and an acrylic monomer such as butyl acrylate. However, it is preferable that the copolymer contains 50% by mass or more of a component derived from styrene.
[0058] The expandable particles and the expanded particles use a composite resin as the base resin as described above, and contain a flame retardant mainly composed of a brominated bisphenol flame retardant in the base resin (i.e., the composite resin). Examples of the brominated bisphenol flame retardant include bisphenol A, bisphenol F, bisphenol S, or brominated derivatives thereof. More specifically, 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane, bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone, 2,2-bis(4-(2,3-dibromopropoxy)-3,5-dibromophenyl)propane, etc. are used. One or more of these brominated flame retardants are used.
[0059] From the viewpoint that excellent flame retardancy can be easily imparted to a molded body even with a small amount of addition, the brominated bisphenol flame retardant contained in the flame retardant is preferably a brominated bisphenol A flame retardant. From the same viewpoint, it is preferable that a brominated bisphenol flame retardant having a 2,3-dibromo-2-methylpropyl group and / or a brominated bisphenol flame retardant having a 2,3-dibromopropyl group is used as the flame retardant, and it is more preferable that 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane is used as the flame retardant.
[0060] The 50% decomposition temperature of the brominated bisphenol flame retardant is preferably 280° C. or more and 340° C. or less, more preferably 285° C. or more and 320° C. or less. In this case, the complex shear viscosity of the composite resin is easily adjusted to a desired range in the temperature range in which the thermal decomposition of the composite resin proceeds. This makes it possible to impart more stable and excellent flame retardancy to the molded product without reducing the expandability of the expandable particles or the retention of the blowing agent. The 50% decomposition temperature of the brominated flame retardant can be measured by a thermogravimetric and differential thermogravimetric analyzer (TG / DTA). Specifically, a differential thermal weight loss curve is measured under the following measurement conditions: heating rate: 10°C / min, measurement temperature range: 40°C to 500°C, in a nitrogen atmosphere, sample pan material: Pt, sample mass: 50 mg, and the temperature at which the weight is reduced by 50% in the differential thermal weight loss curve can be determined as the 50% decomposition temperature.
[0061] The complex shear viscosity η of the composite resin containing the brominated bisphenol flame retardant in the expandable particles is preferably 500 to 5000 Pa·s. When the complex shear viscosity η of the composite resin containing the brominated bisphenol as a flame retardant is in this range, the flame retardancy of the molded body can be improved without decreasing the expandability of the expandable particles. The excellent flame retardancy achieved by using a brominated bisphenol flame retardant and having a complex shear viscosity η in the above range is thought to be expressed as follows. Usually, when a molded body is burned, the vicinity of the burning part of the molded body becomes hot, and the resin near the burning part melts. In this case, if the complex shear viscosity is too low, the fluidity of the molten resin is high, so the molten resin falls off the molded body early, and the burning of the molded body is likely to continue. On the other hand, if the complex shear viscosity is within the above range, the fluidity of the molten resin is relatively low, so the molten resin is likely to remain near the burning part of the molded body. As a result, the vicinity of the burning part is likely to be covered with a coating layer formed of a molten resin containing a brominated bisphenol flame retardant. When such a coating layer containing a brominated bisphenol flame retardant is formed, the vicinity of the burning part is shielded from the flame, so that oxygen is effectively blocked near the burning part, and the thermal decomposition of the resin is suppressed, and the amount of flammable gas generated is thought to be reduced. As a result, combined with the effect of the brominated bisphenol flame retardant blended in the composite resin, the molded body becomes less flammable, and it is thought that excellent flame retardancy can be imparted to the molded body. As described above, when the composite resin contains a brominated bisphenol-based flame retardant as a flame retardant and has a complex shear viscosity η of 500 to 5,000 Pa s, the expandable particles can maintain excellent expandability while stably imparting high flame retardancy to the molded article that meets the flammability test standard FMVSS No. 302 for automotive interior materials.
[0062] In addition, when the flame retardant does not contain a brominated bisphenol flame retardant, for example, when a brominated-styrene-butadiene copolymer as described in Patent Document 1 is used as a flame retardant by blending it with the core particles, even if the complex shear viscosity η is within the above range, it may be difficult to stably exhibit high flame retardancy depending on the expansion ratio, the foaming agent composition, etc. In addition, in order to obtain the desired flame retardancy, for example, it becomes necessary to add a large amount of flame retardant, and this may cause a decrease in the moldability of the expanded beads and the bending properties of the molded body. From the viewpoint of stably increasing the flame retardancy, the complex shear viscosity η of the composite resin containing a brominated bisphenol flame retardant is preferably 600 Pa·s or more, more preferably 800 Pa·s or more, even more preferably 900 Pa·s or more, and particularly preferably 1000 Pa·s or more. From the viewpoint of more stably increasing the expandability of the expandable particles and the in-mold moldability of the expanded particles, the complex shear viscosity η is preferably 4000 Pa·s or less, more preferably 3000 Pa·s or less, even more preferably 2500 Pa·s or less, even more preferably 2000 Pa·s or less, and particularly preferably 1800 Pa·s or less.
[0063] The complex shear viscosity η of the composite resin containing a flame retardant is measured based on JIS K 7244-10:2005. The complex shear viscosity η of the composite resin is a value at an angular frequency of 1 rad / s and a temperature of 300°C. The complex shear viscosity η is a value measured by a viscoelasticity measuring device. In such a measurement, the viscosity of the measurement target can be measured at high temperatures with a small load applied to the measurement target, so that the state of the composite resin during combustion can be suitably evaluated by employing the complex shear viscosity η. In addition, the measurement temperature of the complex shear viscosity η, 300°C, is the temperature immediately before the composite resin starts to thermally decompose. This temperature immediately before (i.e., 300°C) is a suitable temperature for evaluating the state of the composite resin during combustion. The complex shear viscosity η of the composite resin containing the flame retardant can be measured by preparing a measurement sample of a predetermined shape using the expandable particles and performing a predetermined analysis on the measurement sample using a viscoelasticity measuring device. The measurement sample can be prepared, for example, by performing heat press molding on the expandable particles from which the blowing agent has been dispersed.
[0064] The complex shear viscosity η of the composite resin is adjusted to the desired range by adjusting the molecular weight (specifically, the weight average molecular weight Mw) of the styrene resin component, the amount of xylene insoluble matter (i.e., gel) in the composite resin, the mass ratio of the ethylene resin component to the styrene resin component in the composite resin, the type and content of the flame retardant and flame retardant assistant, and the like. For example, with regard to the mass ratio of the ethylene resin component to the styrene resin component in the composite resin, the complex shear viscosity η tends to increase when the mass ratio of the ethylene resin component increases. For example, the complex shear viscosity η tends to increase when the content of the flame retardant and flame retardant assistant is reduced. In addition, the amount of xylene insoluble matter (i.e., gel) in the composite resin can be adjusted, for example, by a combination of polymerization initiators with different hydrogen abstraction capabilities. In addition, the complex shear viscosity η tends to increase by increasing the amount of polymerization initiators with relatively high hydrogen abstraction capabilities.
[0065] The amount of the brominated bisphenol flame retardant in the expandable particles is preferably 0.1 to 3 parts by mass relative to 100 parts by mass of the composite resin. In this case, the flame retardancy of the molded body can be stably increased without decreasing the expandability of the expandable particles or the moldability in the mold of the expanded particles. From the viewpoint of stably increasing the flame retardancy of the molded body, the amount of the brominated bisphenol flame retardant is preferably 0.5 parts by mass or more relative to 100 parts by mass of the composite resin, more preferably 0.6 parts by mass or more, even more preferably 0.8 parts by mass or more, and particularly preferably 1.0 parts by mass or more. In addition, from the viewpoint of further increasing the bending strength of the molded body, the amount of the brominated bisphenol flame retardant is preferably 2.8 parts by mass or less relative to 100 parts by mass of the composite resin, more preferably 2.5 parts by mass or less, even more preferably 2.2 parts by mass or less, and particularly preferably 1.8 parts by mass or less.
[0066] The composite resin preferably contains a radical generator having a 10-hour half-life temperature of 150°C or more as a flame retardant auxiliary. In this case, the flame retardancy can be further improved while suppressing the decrease in toughness of the molded body. In addition, even if the amount of VOC (volatile organic compounds) in the expandable particles is reduced by a stripping treatment described later, a molded body having excellent flame retardancy can be obtained. Specific examples of such flame retardant auxiliary include 2,3-dimethyl-2,3-diphenylbutane, poly(1,4-diisopropylbenzene), 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide. From the viewpoint of obtaining the above effect more stably, it is preferable to use 2,3-dimethyl-2,3-diphenylbutane or poly(1,4-diisopropylbenzene) as the radical generator, and it is more preferable to use 2,3-dimethyl-2,3-diphenylbutane. The 10-hour half-life temperature is defined as the temperature at which 50% of the amount of a radical generator, such as an organic peroxide, charged in an inert solvent is thermally decomposed in 10 hours. The 10-hour half-life temperature can be the value of the 10-hour half-life temperature listed in the catalog or technical documents issued by the manufacturer of the radical generator, such as an organic peroxide.
[0067] In the expandable particles, the mass ratio of the flame retardant assistant to the flame retardant is preferably 0.1 to 1. In this case, the effect of improving the bending strength of the molded article and the flame retardancy of the molded article in a well-balanced manner can be obtained. From the viewpoint of improving this effect, the mass ratio of the flame retardant assistant to the flame retardant is more preferably 0.12 to 0.6, and further preferably 0.15 to 0.5. If the blending amount (by mass) of the flame retardant in the expandable particles is a and the blending amount (by mass) of the flame retardant assistant is b, the mass ratio of the flame retardant assistant to the flame retardant is expressed as b / a. From the same viewpoint, the blending amount of the flame retardant auxiliary is preferably 0.1 to 1 part by mass, more preferably 0.2 to 0.5 parts by mass, and further preferably 0.3 to 0.4 parts by mass, per 100 parts by mass of the composite resin.
[0068] The expandable particles contain a foaming agent. The content of the foaming agent in the expandable particles is preferably 3 to 10% by mass. By setting the content of the foaming agent in this range, the expandable particles have excellent foaming agent retention and expandability. From the viewpoint of further improving this effect, the content of the foaming agent in the expandable particles is preferably 4 to 9% by mass, and more preferably 5 to 8% by mass.
[0069] As the foaming agent, it is preferable to use an organic physical foaming agent, for example, a saturated hydrocarbon having 3 to 6 carbon atoms. In this case, the foamable particles have excellent retention of the foaming agent and excellent foaming properties. Furthermore, the fusion between the foamed particles in the molded product is further improved. As the saturated hydrocarbon, for example, propane, n-butane, isobutane, cyclobutane, n-pentane, isopentane, neopentane, cyclopentane, n-hexane, cyclohexane, etc. can be used. These foaming agents can be used alone or in a mixture of two or more kinds.
[0070] The content of unreacted styrene monomer remaining in the expandable particles is preferably 0 mass ppm or more and 50 mass ppm or less, more preferably 0 mass ppm or more and less than 30 mass ppm, and even more preferably 0 mass ppm or more and 25 mass ppm or less. In this case, a molded article having a low content of VOC (volatile organic compounds) and excellent flame retardancy can be obtained, and a molded article that can be suitably used as a vehicle member or a building member can be obtained. The content of styrene monomer in the expandable particles can be reduced to the above range, for example, by performing a stripping treatment.
[0071] The expandable particles are produced, for example, by carrying out a dispersion step, a modification step, and an impregnation step. In the dispersion step, core particles composed of an ethylene-based resin are dispersed in an aqueous medium. In the modification step, a styrene-based monomer in which a flame retardant is dissolved is added to an aqueous medium, and the core particles are impregnated and polymerized with the styrene-based monomer to obtain composite resin particles in which the composite resin is used as a base resin and the base resin contains a flame retardant. In the impregnation step, the composite resin particles are impregnated with a blowing agent during and / or after polymerization of the composite resin particles.
[0072] The amount of the styrene monomer blended in the modification step relative to 100 parts by mass of the ethylene resin is, for example, from 100 parts by mass to 1900 parts by mass, and particularly preferably from more than 500 parts by mass to 1000 parts by mass.
[0073] The polymerization of the styrene monomer can be carried out in the presence of a flame retardant and a polymerization initiator. As the polymerization initiator, an organic peroxide A having a t-butoxy group and a 10-hour half-life temperature of 80 to 120°C may be used alone, or an organic peroxide A and an organic peroxide B having a t-hexyloxy group or a t-amyloxy group and a 10-hour half-life temperature of 80 to 120°C may be used in combination. When the organic peroxide A and the organic peroxide B are used in combination, it is preferable that the ratio of the amount of the organic peroxide A to the total amount of the organic peroxide A and the organic peroxide B exceeds, for example, 85% by mass. Furthermore, it is preferable to use a brominated bisphenol flame retardant as the flame retardant, and to set the amount of the flame retardant to, for example, 0.1 to 3 parts by mass relative to 100 parts by mass of the total of the ethylene resin and the styrene monomer. In this way, the complex shear viscosity η of the composite resin containing the flame retardant, measured according to JIS K 7244-10:2005 at a frequency of 1 rad / s and a temperature of 300°C, can be adjusted to 500 to 5000 Pa s. By adjusting the blending amount of the organic peroxide having a 10-hour half-life temperature in the above-mentioned predetermined range as described above and adjusting the blending amount of the brominated bisphenol-based flame retardant, the complex shear viscosity η of the composite resin can be adjusted to a desired range.
[0074] Each step will be described in detail below. In the dispersion step, the core particles made of the ethylene-based resin are dispersed in an aqueous medium to obtain a dispersion liquid. For example, a suspending agent, a surfactant, a water-soluble polymerization inhibitor, etc. can be added to the aqueous medium. The ethylene-based resin used for the core particles is as described above.
[0075] A dispersion diameter expanding agent can be added to the core particles. By adding the dispersion diameter expanding agent, for example, the phase consisting of a styrene-based resin component can be enlarged. As the dispersion diameter expanding agent, for example, at least one selected from polystyrene, acrylonitrile-styrene copolymer, rubber-modified polystyrene, ABS resin, and AES resin can be used. An acrylonitrile-styrene copolymer is preferable. When using the dispersion diameter expanding agent, the amount of the dispersion diameter expanding agent is preferably 1 to 10 parts by mass with respect to 100 parts by mass of the ethylene-based resin. In addition, the amount of the acrylonitrile component in the acrylonitrile-styrene copolymer is preferably 20 to 40% by mass.
[0076] The core particles may contain various additives as long as they do not impair the effects of the present invention. Examples of additives include the dispersion diameter expanding agent described above, as well as bubble regulators, pigments, slip agents, antistatic agents, and flame retardants. The core particles can be produced by blending additives added as necessary with an ethylene-based resin, melt-kneading the blend, and then granulating the blend. The melt-kneading can be carried out using an extruder. In order to perform uniform kneading, it is preferable to mix the resin components in advance and then extrude them. The resin components can be mixed using a mixer such as a Henschel mixer, ribbon blender, V blender, or Loedige mixer. The melt-kneading can be carried out using a single-screw extruder or a twin-screw extruder with a high dispersion type screw such as a Dulmage type, Madoc type, or Unimelt type.
[0077] The addition of a bubble regulator can adjust the bubble diameter of the expanded beads after expansion. Examples of the bubble regulator include organic substances such as higher fatty acid bisamide, higher fatty acid metal salt, and PTFE; and inorganic substances such as talc, silica, zinc borate, and alum. When an organic bubble regulator is used, the blending amount is preferably in the range of 0.01 to 2 mass% relative to 100 mass% of the core particles. When an inorganic bubble regulator is used, the blending amount is preferably in the range of 0.1 to 5 mass parts relative to 100 mass% of the core particles. By adjusting the blending amount of the bubble regulator within the above range, the bubble diameter of the expanded beads and the molded product becomes good, the bubbles are less likely to be destroyed during molding in the mold, and the appearance of the molded product becomes better.
[0078] The granulation of the core particles can be carried out by, for example, a strand cut method, an underwater cut method, a hot cut method, etc. Any other method can also be used as long as it can produce core particles having the desired particle size and particle weight.
[0079] The particle diameter of the core particles is preferably 0.1 mm or more, and more preferably 0.3 mm or more. In this case, the composite resin particles obtained after impregnation and polymerization of the styrene monomer can be made large enough to sufficiently retain the foaming agent. In addition, from the viewpoint of preventing the foamed particles from impairing the filling ability into the mold during in-mold molding, the particle diameter of the core particles is preferably 3.0 mm or less, more preferably 1.5 mm or less, and even more preferably 1.2 mm or less. The particle weight of the core particles is preferably 0.5 mg / piece or less, more preferably 0.4 mg / piece or less, and even more preferably 0.3 mg / piece or less. In this case, even if the amount of styrene monomer impregnated into the core particles increases, the styrene monomer is easily impregnated sufficiently into the inside of the core particles, and uneven impregnation between particles is unlikely to occur, making it easier to stably obtain the desired expandable particles. The particle weight of the core particles is preferably 0.01 mg / piece or more, more preferably 0.05 mg / piece or more, and even more preferably 0.1 mg / piece or more. In this case, coagulation during polymerization can be stably suppressed.
[0080] When an extruder is used to granulate the core particles, the particle size and particle weight of the core particles can be adjusted, for example, by adjusting the amount of resin extruded and the cutting speed of the resin when the resin is extruded and cut through holes having an aperture size within the range of the desired particle size. The particle size of the core particles can be measured, for example, as follows. That is, the core particles are observed using a microscope photograph, and the maximum diameter of each of 200 or more core particles is measured, and the arithmetic average value of the maximum diameters is taken as the particle size of the core particles.
[0081] In the dispersion step, the core particles are dispersed in an aqueous medium to prepare a dispersion liquid. Dispersion of the core particles in the aqueous medium can be carried out, for example, in a closed vessel equipped with a stirrer. The closed vessel is, for example, a pressurized vessel. The aqueous medium can be, for example, a liquid such as deionized water.
[0082] The core particles are preferably dispersed in an aqueous medium together with a suspending agent. As the suspending agent, for example, tricalcium phosphate, hydroxyapatite, magnesium pyrophosphate, magnesium phosphate, aluminum hydroxide, ferric hydroxide, titanium hydroxide, magnesium hydroxide, barium phosphate, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, talc, kaolin, bentonite, and other fine particle inorganic suspending agents can be used. In addition, for example, organic suspending agents such as polyvinylpyrrolidone, polyvinyl alcohol, ethyl cellulose, and hydroxypropylmethylcellulose can also be used. Tricalcium phosphate, hydroxyapatite, and magnesium pyrophosphate are preferable. As the suspending agent, one type of substance may be used, or two or more types of substances may be used.
[0083] The amount of the suspending agent used is preferably 0.05 to 10 parts by mass in terms of solid content per 100 parts by mass of the aqueous medium of the suspension polymerization system (specifically, all water in the system including water such as the reaction product-containing slurry). More preferably, it is 0.3 to 5 parts by mass. By setting the amount of the suspending agent within the above range, the styrene monomer can be stably suspended, the generation of resin lumps can be prevented, and the particle size distribution of the expandable particles can be suppressed from widening.
[0084] A surfactant can be added to the aqueous medium. As the surfactant, for example, an anionic surfactant, a nonionic surfactant, a cationic surfactant, or an amphoteric surfactant is preferably used. These surfactants can be used alone or in combination. Among these, it is preferable to use an anionic surfactant from the viewpoint of dispersion stability.
[0085] Furthermore, electrolytes made of inorganic salts such as lithium chloride, potassium chloride, sodium chloride, sodium sulfate, sodium nitrate, sodium carbonate, and sodium bicarbonate may be added to the aqueous medium as necessary.
[0086] It is preferable to add a water-soluble polymerization inhibitor to the aqueous medium. In this case, the polymerization of the styrene monomer in the form of microdroplets present in the aqueous medium and the styrene monomer present near the surface of the core particles is suppressed. As a result, the expanded beads have excellent moldability in the mold, and the molded product has excellent mechanical strength such as toughness.
[0087] Examples of the water-soluble polymerization inhibitor that can be used include sodium nitrite, potassium nitrate, ammonium nitrite, L-ascorbic acid, and citric acid. The amount of the water-soluble polymerization inhibitor added is preferably 0.001 to 0.1 parts by mass, and more preferably 0.002 to 0.03 parts by mass, per 100 parts by mass of the aqueous medium (specifically, all water in the system including water such as the reaction product-containing slurry). In this case, the amount of the remaining styrene monomer in the expandable particles can be reduced.
[0088] In the modification step, the core particles are impregnated with a styrene-based monomer in an aqueous medium, and the styrene-based monomer is polymerized. At this time, it is preferable to impregnate the core particles with the styrene-based monomer in which a flame retardant is dissolved. As the styrene-based monomer, for example, styrene can be used. As the styrene-based monomer, a monomer copolymerizable with styrene and styrene can be used in combination. The styrene-based monomer may be one type or two or more types.
[0089] Examples of monomers copolymerizable with styrene include the following styrene derivatives and other vinyl monomers, etc. Examples of styrene derivatives include α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-methoxystyrene, pn-butylstyrene, pt-butylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,4,6-tribromostyrene, divinylbenzene, styrenesulfonic acid, and sodium styrenesulfonate.
[0090] Other vinyl monomers include acrylic acid esters, methacrylic acid esters, vinyl compounds containing a hydroxyl group, vinyl compounds containing a nitrile group, organic acid vinyl compounds, olefin compounds, diene compounds, vinyl halide compounds, vinylidene halide compounds, and maleimide compounds.
[0091] From the viewpoint of increasing the foaming property after the foaming agent is impregnated, it is preferable to use polystyrene or a copolymer of styrene and an acrylic acid ester as the styrene-based resin component. Examples of the acrylic acid ester include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate. Among them, it is preferable to use butyl acrylate as the acrylic acid ester. The content of the butyl acrylate component in the composite resin is preferably 0.2 to 5 mass % based on the entire composite resin, more preferably 0.3 to 3 mass %, and even more preferably 0.5 to 2 mass %. In this case, the foaming property of the expandable particles can be improved. In addition, the glass transition temperature of the styrene-based resin component can be increased, and an expanded particle molding having excellent compression properties and excellent heat resistance in a high-temperature environment (for example, 80°C) can be obtained.
[0092] The polymerization of the styrene monomer can be carried out in the presence of a polymerization initiator as described above. In this case, crosslinking may occur along with the polymerization of the styrene monomer. A polymerization initiator is used in the polymerization of the styrene monomer, and a crosslinking agent can be used in combination as necessary. When using a polymerization initiator or a crosslinking agent, it is preferable to dissolve the polymerization initiator and the crosslinking agent in the styrene monomer in advance.
[0093] As the polymerization initiator, those used in the suspension polymerization method of styrene-based monomers can be used. For example, those soluble in vinyl monomers such as styrene-based monomers can be used. As the polymerization initiator, as described above, organic peroxide A having a t-butoxy group and a 10-hour half-life temperature of 80 to 120°C may be used alone, or organic peroxide A may be used in combination with organic peroxide B having a t-hexyloxy group or a t-amyloxy group and a 10-hour half-life temperature of 80 to 120°C. As the organic peroxide A, t-butylperoxy-2-ethylhexyl monocarbonate, t-butylperoxy-2-ethylhexanoate, t-butylperoxy laurate, t-butylperoxy isopropyl monocarbonate, t-butylperoxy benzoate, di-t-butyl peroxide, 1,1-bis(t-butylperoxy)cyclohexane, etc. can be used. As the organic peroxide B, t-hexyl peroxybenzoate, t-hexyl peroxy isopropyl monocarbonate, di-t-hexyl peroxide, etc. can be used. As the organic peroxide B having a t-amyloxy group, for example, t-amyl peroxy isopropyl monocarbonate, t-amyl peroxy-2-ethylhexyl monocarbonate, t-amyl peroxy benzoate, 1,1-bis(t-amyl peroxy)cyclohexane, t-amyl peroxy acetate, etc. can be used. As the polymerization initiator, one type may be used, or two or more types may be used. The polymerization initiator can be used in an amount of, for example, 0.1 to 1.0 part by mass, preferably 0.2 to 0.8 parts by mass, more preferably 0.3 to 0.7 parts by mass, and preferably 0.4 to 0.6 parts by mass, relative to 100 parts by mass of the styrene-based monomer. In this case, the amount of unreacted styrene-based monomer remaining in the expandable particles can be reduced. In addition, while maintaining the expandability of the expandable particles and the moldability of the expanded particles, the complex shear viscosity of the composite resin under specified conditions can be increased, and the xylene insoluble content can be increased, thereby improving the flame retardancy of the molded article.
[0094] As described above, from the viewpoint of easily increasing the complex shear viscosity of the composite resin under predetermined conditions, the ratio of the amount of organic peroxide A to the total amount of organic peroxide A and organic peroxide B is preferably more than 85 mass%, more preferably 86 mass% or more, and even more preferably 90 mass% or more. On the other hand, from the viewpoint of obtaining a molded product having good expandability of the expandable particles, excellent in-mold moldability of the expanded particles, and superior bending strength, the ratio of the amount of organic peroxide A to the total amount of organic peroxide A and organic peroxide B is preferably 98 mass% or less, more preferably 96 mass% or less, and even more preferably 95 mass% or less.
[0095] In addition, the crosslinking agent used is one that does not decompose at the polymerization temperature but decomposes at the crosslinking temperature. For example, one whose 10-hour half-life temperature is 5°C to 50°C higher than the polymerization temperature can be used. Specifically, peroxides such as dicumyl peroxide, 2,5-t-butyl perbenzoate, and 1,1-bis-t-butylperoxycyclohexane can be used. One type of crosslinking agent may be used, or two or more types may be used. The amount of the crosslinking agent is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the styrene monomer. The polymerization initiator and the crosslinking agent may be the same compound.
[0096] A bubble regulator can be added to the styrene monomer. Examples of the bubble regulator include fatty acid monoamide, fatty acid bisamide, talc, silica, polyethylene wax, methylene bisstearic acid, methyl methacrylate copolymer, and silicone. Examples of the fatty acid monoamide include oleic acid amide and stearic acid amide. Examples of the fatty acid bisamide include ethylene bisstearic acid amide.
[0097] Furthermore, to the styrene monomer, a plasticizer, an oil-soluble polymerization inhibitor, a dye, etc. can be added as necessary within the range not impairing the effect of the present invention.
[0098] When the core particles are impregnated with the styrene monomer and polymerized, the entire amount can be added at once, or it can be added in several batches. When adding in several batches, the styrene monomer can be divided into several monomers such as a first monomer and a second monomer, and these monomers can be added to the aqueous medium at different times and temperatures. By adding in several batches, it is possible to prevent the generation of resin lumps in the modification process.
[0099] In the modification step, the polymerization temperature varies depending on the type of polymerization initiator used, but is preferably 80°C to 130°C.
[0100] In the impregnation step, the foaming agent is impregnated. The foaming agent can be impregnated into the particles during or after the polymerization of the styrene monomer. The foaming agent may be impregnated into both the particles during polymerization and the particles after polymerization. Specifically, the foaming agent is pressed into a container that contains the particles after polymerization during polymerization, and the foaming agent is impregnated into the particles. The foaming agent is as described above.
[0101] The impregnation temperature of the foaming agent is preferably within the range of (Tg-10)°C to (Tg+40)°C, and more preferably within the range of (Tg-5)°C to (Tg+25)°C, where Tg (unit: °C) is the glass transition temperature of the styrene-based resin component. The glass transition temperature (Tg) of the styrene-based resin component can be measured by the method described above.
[0102] After impregnation with the foaming agent, the expandable particles are dehydrated and dried, and the expandable particles can be coated with a surface coating agent as required. Examples of the surface coating agent include zinc stearate, stearate triglyceride, stearate monoglyceride, and hardened castor oil. The amount of the surface coating agent added is preferably 0.01 to 2 parts by mass per 100 parts by mass of the expandable particles.
[0103] Expandable particles can be obtained by heating and expanding the expandable particles with a heating medium. Specifically, a heating medium such as steam is introduced into a pre-expansion machine to which the expandable particles have been supplied, and the expandable particles are pre-expanded to obtain the expanded particles. The organic physical blowing agent contained in the expandable particles usually remains in the expanded particles obtained in this manner.
[0104] The bulk density of the foam particles is 15 to 45 kg / m 3 It is preferable that the bulk density of the expanded beads is 16 to 40 kg / m. By molding such expanded beads in a mold, a molded article that is lightweight and has excellent mechanical properties such as toughness and rigidity can be obtained. Even if the expandable beads are expanded to a low bulk density within the above range, the expanded beads and the molded article can exhibit excellent flame retardancy. From the viewpoint of improving such effects, the bulk density of the expanded beads is preferably 16 to 40 kg / m. 3 More preferably, it is 18 to 35 kg / m 3 More preferably, it is 20 to 30 kg / m 3 It is particularly preferable that the bulk density of the expanded particles (unit: kg / m 3 ) is calculated by preparing a 1 L measuring cylinder, filling the empty measuring cylinder with expanded particles up to the 1 L mark, measuring the mass of expanded particles per 1 L (unit: g), and converting the unit. EXAMPLES
[0105] Example 1 [Creation of core particles] As an ethylene-based resin, a linear low-density polyethylene (Nipolon (registered trademark) Z HF210K manufactured by Tosoh Corporation) polymerized using a metallocene polymerization catalyst was prepared. The linear low-density polyethylene is hereinafter referred to as "LLDPE" as appropriate. The melting point Tm of this LLDPE is 103°C. In addition, an acrylonitrile-styrene copolymer (AS-XGS manufactured by Denka Co., Ltd., weight average molecular weight: 109,000, acrylonitrile content: 28% by mass, MFR (200°C, 5 kgf): 2.8 g / 10 min) was prepared as a dispersion diameter expanding agent. In addition, a master batch of an antioxidant (TMB113 manufactured by Toho Co., Ltd., linear low-density polyethylene: 90% by mass, phosphorus-based stabilizer: 6.5% by mass, hindered phenol-based antioxidant: 3.5% by mass) was prepared. Furthermore, a mixed master batch (ethylene bis-stearic acid amide: 10 mass%, zinc 12-hydroxystearate: 3 mass%, linear low-density polyethylene: 87 mass%) of ethylene bis-stearic acid amide (Kaowax EB-FF manufactured by Kao Corporation) as a foam regulator and zinc 12-hydroxystearate (ZS-6 manufactured by Nitto Chemical Industry Co., Ltd.) as a lubricant was prepared. Then, 87.7 kg of ethylene resin, 4.7 kg of acrylonitrile-styrene copolymer as a dispersion diameter expander, 0.9 kg of antioxidant master batch, and 6.7 kg of a mixed master batch of a cell regulator and a lubricant were charged into a Henschel mixer (FM-75E manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) and mixed for 5 minutes. Next, the mixture was melt-kneaded at a barrel temperature of 220 to 250° C. using a single-screw extruder (PMS50-28 manufactured by IKG Corporation) with an inner barrel diameter of 50 mm, and cut into particles by an underwater cutting method to obtain core particles of an average weight of 0.2 mg / piece.
[0106] [Preparation of composite resin particles] 1000g of deionized water and 6.0g of sodium pyrophosphate were placed in a 3L autoclave equipped with a stirrer. Then, 12.9g of magnesium nitrate hexahydrate was added and stirred at room temperature for 30 minutes to prepare magnesium pyrophosphate slurry as a suspension. Next, 2g of sodium alkylsulfonate (10% aqueous solution of Latemul (registered trademark) PS manufactured by Kao Corporation) as a surfactant, 0.15g of sodium nitrite as a water-soluble polymerization inhibitor, and 75g of core particles were placed in the autoclave.
[0107] Next, 0.21 g of t-hexyl peroxybenzoate (Perhexyl (registered trademark) Z manufactured by NOF Corp.) as a polymerization initiator, 2.50 g of t-butylperoxy-2-ethylhexyl monocarbonate (Perbutyl (registered trademark) E manufactured by NOF Corp.), 6.67 g of 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane (SR130 manufactured by Daiichi Kogyo Seiyaku Co., Ltd. (50% decomposition temperature: 294 ° C.)) as a bromine-based flame retardant, and 1.67 g of 2,3-dimethyl-2,3-diphenylbutane (Nofumer (registered trademark) BC-90 manufactured by NOF Corp. (10-hour half-life temperature: 210 ° C.)) as a flame retardant aid were dissolved in the first monomer (styrene-based monomer). Then, this dissolved matter was charged into the autoclave while stirring at a stirring speed of 500 rpm. As the first monomer, a mixed monomer of 70 g of styrene and 5 g of butyl acrylate was used.
[0108] Next, the air in the autoclave was replaced with nitrogen, and then heating was started, and the temperature in the autoclave was raised to 100°C over 1.5 hours. It was further held at 100°C for 1 hour. Thereafter, the stirring speed was reduced to 450 rpm, and it was held at 100°C for 7.5 hours. One hour after reaching 100°C, 350g of styrene was added to the autoclave as a second monomer (specifically, a styrene-based monomer) over 5 hours. The mass ratio of the blended amounts of the core particles, monomer, polymerization initiator, flame retardant, and flame retardant assistant is as shown in Table 1.
[0109] The temperature inside the autoclave was then raised to 125°C over 2 hours and held at 125°C for 5 hours. The autoclave was then cooled over 1 hour, and the composite resin particles were removed. Nitric acid was then added to dissolve the magnesium pyrophosphate adhering to the surface of the composite resin particles. The particles were then dehydrated and washed using a centrifuge, and the moisture adhering to the surface was removed using an airflow dryer.
[0110] [Stripping and foaming agent impregnation] In a 3L autoclave equipped with a stirrer, 1030g of deionized water was put in, 1.03g of calcium phosphate tribasic (manufactured by Taihei Chemical Industry Co., Ltd.) as a suspending agent, 1.03g of disodium alkyl diphenyl ether disulfonate (Pelex (registered trademark) SSH 1% aqueous solution manufactured by Kao Corporation) as a surfactant, and 670g of the composite resin particles produced above were put in and stirred at a stirring speed of 400 rpm. Next, the air in the autoclave was replaced with nitrogen, and then heating was started, and the temperature in the autoclave was raised to 130°C over 1 hour and maintained at 130°C for 5 hours. During this time, the vent line of the autoclave was slightly opened, the internal pressure was maintained at 0.12MPa (gauge pressure), and volatile organic compounds (VOCs) such as styrene monomers contained in the composite resin particles were distilled out by steam distillation. After holding for 5 hours, the temperature in the autoclave was cooled to 90°C. When the temperature reached 90°C, the vent line was closed to seal the autoclave, and 10.0 g of pentane (a mixture of about 80% by mass of normal pentane and about 20% by mass of isopentane) and 65.0 g of isobutane were added to the autoclave over about 20 minutes (foaming agent impregnation step). The mixture was kept at 90°C for 3 hours, and then heated to 105°C over 1 hour, and kept at 105°C for 5 hours, and then cooled to 30°C over about 2.5 hours.
[0111] The expandable particles were then removed from the autoclave, and nitric acid was added to dissolve the tribasic calcium phosphate adhering to the surface of the expandable particles. The particles were washed with water and dehydrated using a centrifuge, and the water adhering to the surface was removed using an airflow dryer. The mass ratio of the styrene-based monomer and the ethylene-based resin used during production was taken as the mass ratio of the component derived from the styrene-based monomer and the component derived from the ethylene-based resin in the composite resin.
[0112] Next, the expandable granules obtained by the above method were put into a normal pressure batch expansion machine with a volume of 30 L, and steam was supplied from the bottom of the expansion machine to expand the granules until the bulk density reached about 33 kg / m 3 The bulk density was determined by drying the obtained expanded beads at room temperature for one day, filling a 1-L measuring cylinder with the expanded beads up to the 1-L mark, and measuring the mass (unit: g) of the expanded beads per 1 L.
[0113] Next, using a mold molding machine (DSM-0705VS manufactured by DABO Corporation), the expanded particles were dried at room temperature for one day after foaming to form a rectangular solid molded body of 300 mm × 75 mm × 25 mm and a box-shaped molded body of 340 mm × 270 mm × 150 mm with a wall thickness of 25 mm. The obtained molded bodies were dried at 40°C for one day, then aged at 60°C for one day, and further aged at 80°C for two days, after which various evaluations were performed.
[0114] Using the expandable particles and molded bodies obtained as described above, the average particle size (d63), the foaming agent content, the content of xylene insolubles (XY gel content), the weight average molecular weight Mw of the tetrahydrofuran solubles, the glass transition temperature (Tg) of the methyl ethyl ketone solubles, the content R-SM of the residual styrene monomer, the complex viscosity η at 300°C, the apparent density, the 50% compressive stress σ23 at a temperature of 23°C, the 50% compressive stress σ80 at a temperature of 80°C, the breaking strain, the bending modulus, and the maximum bending stress were measured as follows, and the flame retardancy of the molded bodies was evaluated as follows. The results are shown in Table 2. The symbols in the table have the following meanings. T 1 / 2 : 10 hour half-life temperature R-SM: Amount of unreacted styrene monomer remaining in the expandable particles or molded body BE: t-Butylperoxy-2-ethylhexyl monocarbonate HZ: t-Hexyl peroxybenzoate SR130: 2,2-bis[4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl]propane FCP-65CN: Bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone BC: 2,3-dimethyl-2,3-diphenylbutane E3000: Brominated styrene-butadiene copolymer
[0115] ·Average particle diameter (d63) The average particle size (d63) of the expandable particles was calculated using a dry particle size distribution analyzer (Militrack JPA, manufactured by Nikkiso Co., Ltd.) as the particle size value (d63) at which the weight cumulative particle size value from the minimum particle size reaches 63%.
[0116] Foaming agent content Using expandable particles or molded bodies as samples, the foaming agent content was measured by the following method. First, about 1 g of the sample was placed in an aluminum dish and heated in a dryer at 120°C for 4 hours to evaporate the volatile matter (including moisture and foaming agent). The amount of volatile matter in the sample was calculated from the weight difference before and after heating. Separately from the measurement of the amount of volatile matter, about 0.3 g of the sample was weighed and the water content in the sample was determined using a Karl Fischer moisture meter. The amount of the foaming agent in the expandable particles or molded article was calculated by subtracting the amount of water (unit: mass%) from the amount of volatile matter (unit: mass%) of the sample calculated as above. That is, the amount of the foaming agent in the expandable particles or molded article can be calculated by the following formula. Foaming agent content (mass%) = Volatile content (mass%) - Water content (mass%)
[0117] Xylene insoluble matter content (XY gel content) 0.5 g of the molded body was placed in a 150 mesh wire bag. Next, about 95 ml of xylene was placed in a 200 ml round bottom flask, and the wire bag was set in a Soxhlet extraction tube to perform Soxhlet extraction. After the extraction was completed, it was cooled to room temperature, the wire net was removed from the extraction tube, and the xylene insolubles were washed together with the wire net with about 400 ml of acetone. After air drying, the xylene insolubles were dried for 4 hours in a dryer at a temperature of 120°C. The mass ratio of the xylene insolubles (unit: g) to 0.5 g of the molded body was expressed as a percentage, and was taken as the content of the xylene insolubles, i.e., the XY gel amount (unit: mass%). The xylene insolubles are mainly crosslinked ethylene resin components in the composite resin.
[0118] Weight average molecular weight (Mw) of tetrahydrofuran solubles Approximately 35 mg of the molded body and approximately 10 mL of tetrahydrofuran (THF) were placed in a 10 mL measuring flask and allowed to stand for 24 hours. After that, the THF insoluble matter was removed using a membrane filter (0.45 μm) and the THF soluble matter was collected. The molecular weight of this THF soluble matter was measured by gel permeation chromatography (GPC) and calibrated with standard polystyrene to obtain Mw. The THF soluble matter in the composite resin was mainly a styrene-based resin component. The measurement conditions for the GPC method were as follows. GPC equipment: Tosoh Corporation HLC-8320GPC EcoSEC Detector: Differential refractometer (RI) Column: Tosoh Corporation TSKguardcolumn SuperH-H x 1 TSK-GEL SuperHM-H x 2 connected in series Column temperature: 40°C, eluent: THF, flow rate: 0.6 ml / min, sample concentration: 0.1 wt%
[0119] Glass transition temperature (Tg) of methyl ethyl ketone solubles 2.0 g of the molded body and 30 mL of methyl ethyl ketone (MEK) were placed in a 100 mL beaker and stirred at room temperature for one day. After filtering the MEK solution, the filtrate was dropped into 100 mL of methanol. The MEK soluble matter precipitated in the methanol was collected and then dried at 60°C for 24 hours. The MEK soluble matter collected in this manner was mainly composed of styrene-based resin components. 2 to 4 mg of the obtained MEK soluble matter was used as a sample, and differential scanning calorimetry was performed in accordance with JIS K7121:1987, and a DSC curve was obtained under the condition of a heating rate of 20°C / min. The midpoint glass transition temperature in this DSC curve was taken as the glass transition temperature (Tg) of the MEK soluble matter, that is, the styrene-based resin component. The differential scanning calorimetry was performed using a 250-type DSC measuring instrument manufactured by TA Instruments Co., Ltd.
[0120] Unreacted styrene content (R-SM) The expandable particles or molded body was used as a sample, and the content of unreacted styrene in the sample was measured using a headspace gas chromatograph mass spectrometer. Specifically, standard solutions were prepared so that the styrene concentration in DMF was 5 mass ppm, 50 mass ppm, and 500 mass ppm. 0.2 g of the standard solution was precisely weighed into a 20 ml vial, and 5 ml of DMF was added and sealed. The gas phase was measured using a gas chromatograph mass spectrometer, and a calibration curve was created from the obtained chromatogram. In addition to the preparation of the calibration curve, 0.2 g of freeze-pulverized expandable particles or 0.2 g of molded body was precisely weighed into a 20 ml vial, and 5 ml of DMF was added and sealed, and the vial was kept at room temperature for one day. The gas phase was measured using a gas chromatograph mass spectrometer. The peak area derived from styrene in the chromatogram obtained above was converted to mass using a calibration curve created in advance, and the content of unreacted styrene in the sample was determined.
[0121] The measurement conditions for gas chromatography mass spectrometry were as follows. Gas chromatograph mass spectrometer: Shimadzu Corporation GCMS-QP2020 Headspace sampler: Shimadzu Corporation HS-20 Capillary column: GL Sciences, Inc., Stabilwax, inner diameter 0.32 mm, length 30 m Headspace sampler incubation conditions: 90℃, 1 hour Column temperature: 50°C x 2 min → (10°C / min) → 90°C → (5°C / min) → 120°C → (20°C / min) → 230°C x 2 min Ion source temperature: 200℃ Carrier gas: Helium, column flow rate 2ml / min Split ratio: 1 / 10
[0122] Complex shear viscosity (η) The obtained expandable particles were dried at 60°C for one day under normal pressure to dissipate the foaming agent. After drying, 35 g of the dried expandable particles were heat-pressed at 200°C using a heat press machine (HF-37 manufactured by Shinto Metal Industries Co., Ltd.) equipped with a mold measuring 150 mm in length and 150 mm in width, to produce a flat plate with a thickness of about 1.0 to 1.5 mm. The flat plate was cut to a diameter of 25 mm to prepare a measurement sample. The obtained sample was subjected to dynamic viscoelastic analysis using a rheometer (viscoelasticity measuring device) based on JIS K 7244-10:2005 to determine the complex shear viscosity η at an angular frequency of 1 rad / s and a temperature of 300°C. The complex shear viscosity η was determined 600 seconds after the start of the dynamic viscoelastic analysis. This measurement was performed on three different test samples, and the arithmetic mean of the measured values was calculated. The value was rounded off to the nearest tenth, and this value was regarded as the complex shear viscosity of the composite resin containing the flame retardant.
[0123] The measurement conditions for the complex shear viscosity η are as follows: Rheometer: DISCOVERY HR-2 manufactured by TA Instruments Co., Ltd. Geometry: φ25mm parallel plate Measurement temperature: 300℃ Angular frequency: 1rad / s Distortion: 0.1% Gap: 0.8mm Measurement atmosphere: Nitrogen flow
[0124] Apparent density Apparent density of the compact (kg / m 3 ) was obtained by measuring the mass of the rectangular parallelepiped molded body, dividing the mass by the volume of the molded body, and converting the mass into units.
[0125] 50% compressive stress Plate-shaped test pieces measuring 50 mm in length, 50 mm in width, and 25 mm in thickness were cut out from the rectangular solid-shaped molded body, and compression tests were performed in accordance with JIS K 7220: 2006. The compressive stress when the compressive strain was 50% was the 50% compressive stress (unit: kPa), and the 50% compressive stress when the test conditions were 23°C was σ23, and the 50% compressive stress when the test conditions were 80°C was σ80. For measurements in an 80°C atmosphere, the measurement sample was left to stand in a dryer at 80°C for 24 hours in advance to condition the measurement sample before measurements were performed.
[0126] Flexural modulus, strain at break, maximum bending stress A molded body having a length of 300 mm, a width of 75 mm, and a thickness of 25 mm and having a skin surface on the entire surface, that is, a surface that was in contact with the molding surface of the mold during molding in the mold, was prepared. A three-point bending test was performed on this molded body in accordance with JIS K 7221-2:2006 under the conditions of a support distance of 200 mm, a pressure wedge of 10R and a support stand of 10R, and a descent speed of the pressure wedge of 10 mm / min, to measure the bending strength. A stress-strain curve was obtained from the stress (unit: kPa) and strain (unit: %) obtained by the measurement. From the obtained stress-strain curve, the bending modulus of the molded body, the breaking strain which is the strain of the molded body at the time when the molded body breaks, and the maximum bending stress (bending strength) which is the point at which the molded body shows the maximum stress were obtained. The breaking strain (unit: %) was calculated by 6 × thickness of molded body (unit: mm) × deflection amount of molded body at break (unit: mm) ÷ (support distance (unit: mm)) 2 It is calculated by multiplying by 100.
[0127] Flame retardant Two types of test pieces with different thicknesses were cut out from the bottom plate of the box-shaped molded body after conditioning, and the flame retardancy was evaluated using these test pieces. Specifically, rectangular parallelepiped test piece A with dimensions of 340 mm length, 102 mm width, and 12.7 mm thickness and rectangular parallelepiped test piece B with dimensions of 340 mm length, 102 mm width, and 7.5 mm thickness were cut out from the bottom plate of the box-shaped molded body, and 10 pieces of each were prepared. Using these test pieces, a flammability test was performed according to the method specified in FMVSS (Federal Motor Vehicle Safety Standards) No. 302.
[0128] Specifically, one end of the test piece in the vertical direction was attached to a clamp or the like, and the test piece was held horizontally. A burner flame was applied to the other end of the test piece in the vertical direction, i.e., the end not held by the clamp, for 15 seconds, and then the burner flame was removed from the test piece. The height of the burner flame was 38 mm, and the distance from the tip of the burner to the bottom surface of the test piece was 19 mm.
[0129] Then, the measurement of the burning time was started when the flame generated from the test specimen reached a position 38 mm away from the open end of the test specimen (i.e., the end of the test specimen in the vertical direction that is not held by a clamp, etc.). If the flame generated from the test specimen then reached a position 38 mm away from the fixed end of the test specimen (i.e., the end of the test specimen in the vertical direction that is held by a clamp, etc.), the measurement of the burning time was completed when the flame reached that position. If the burning of the test specimen ended before it reached a position 38 mm away from the fixed end of the test specimen, the measurement of the burning time was completed when the burning ended. If the burning of the test specimen ended before it reached a position 38 mm away from the open end of the test specimen, the burning time of the test specimen was treated as 0 seconds.
[0130] The above tests were carried out 10 times for each of test pieces A and B, and the flame retardancy was evaluated based on the test results. The symbols shown in the "Flame retardancy (test piece A)" column in Table 2 have the following meanings: A: All of the test results for the 10 test pieces A met one of the following conditions (1a) to (1c): (1a) the test piece did not ignite, (1b) the burning of the test piece ended before it reached the position where the burning time measurement started (i.e., the position 38 mm away from the open end of the test piece), and (1c) the burning of the test piece ended within 60 seconds after it reached the position where the burning time measurement started, and the distance from the measurement start position to the burning end position was within 51 mm. B: The test results of 10 test pieces A included test results that did not fall under the above conditions (1a) to (1c), and the burning rate was 60 mm / min or less. C: The test results of 10 test pieces A included test results that did not fall under the above conditions (1a) to (1c), and the burning rate exceeded 60 mm / min.
[0131] The symbols shown in the "Flame retardancy (test piece B)" column in Table 2 have the following meanings: A: All of the test results for the 10 test pieces B meet any of the above conditions (1a) to (1c), namely, (1a) the test piece does not ignite, (1b) the test piece stops burning before it reaches the position where the burning time measurement starts, and (1c) the test piece stops burning within 60 seconds after it reaches the position where the burning time measurement starts, and the distance from the measurement start position to the position where the burning ends is within 51 mm, or, among the test results for the 10 test pieces B, there is a test result that does not meet the above conditions (1a) to (1c), but the burning rate is 60 mm / min or less. B: The test results of 10 test pieces B included test results that did not fall under the above conditions (1a) to (1c), and the burning rate was greater than 60 mm / min and less than 102 mm / min. C: The test results of 10 test pieces B did not fall under the above conditions (1a) to (1c), and the burning rate exceeded 102 mm / min.
[0132] The burning rate used in the above evaluation is the arithmetic mean of the burning rates of the 10 test pieces in the flammability test. When calculating the burning rate used in the evaluation, the burning rate of the test piece that fell under any of the above conditions (1a) to (1c) in the flammability test was treated as 0 mm / min. The burning rate of the test piece that did not fall under the above conditions (1a) to (1c) was calculated by the following formula (I). B=60×D / T (I) In the above formula (I), the symbol B means the burning rate (unit: mm / min), the symbol D means the distance the flame traveled (unit: mm), and the symbol T means the time required for the flame to travel D mm (unit: seconds).
[0133] Example 2 In this example, the amount of t-hexyl peroxybenzoate used in producing the composite resin particles in Example 1 was changed from 0.21 g to 0.42 g, and the amount of 2,3-dimethyl-2,3-diphenylbutane used as a flame retardant aid was changed from 1.67 g to 0 g, except that the expandable particles, expanded particles, and molded bodies were produced in the same manner as in Example 1.
[0134] Example 3 In this example, the expandable particles, expanded particles, and molded bodies were prepared in the same manner as in Example 1, except that the amount of styrene used as the first monomer in preparing the composite resin particles in Example 1 was changed from 70 g to 75 g, the amount of butyl acrylate used was changed from 5 g to 0 g, and the amount of t-hexyl peroxybenzoate used was changed from 0.21 g to 0.42 g.
[0135] Example 4 In this example, the amount of core particles used in producing the composite resin particles in Example 1 was changed from 75 g to 125 g, the amount of t-hexyl peroxybenzoate used was changed from 0.21 g to 0.42 g, and the amount of styrene used as the first monomer was changed from 70 g to 60 g, and the amount of butyl acrylate used was changed from 5 g to 15 g, except that the expandable particles, expanded particles, and molded bodies were produced in the same manner as in Example 1.
[0136] Example 5 In this example, the amount of the mixed master batch of the cell regulator and lubricant used in the preparation of the core particles in Example 1 was changed from 6.7 kg to 10 kg, the amount of t-butylperoxy-2-ethylhexyl monocarbonate used in the preparation of the composite resin particles in Example 1 was changed from 0.21 g to 0.24 g, the amount of t-hexyl peroxybenzoate used was set to 0 g, the amount of 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane used as the bromine-based flame retardant was changed from 6.67 g to 10.3 g, and isobutane as the blowing agent was changed to mixed butane (a mixture of approximately 67% by mass of normal butane and approximately 33% by mass of isobutane). Except for the above, the obtained molded bodies were cured at 40°C for 3 days and then various evaluations were performed. Except for this, expandable particles, expanded particles, and molded bodies were prepared in the same manner as in Example 1.
[0137] Comparative Example 1 In this example, the amount of t-hexyl peroxybenzoate used in producing the composite resin particles in Example 1 was changed from 0.21 g to 1.25 g, the amount of t-butylperoxy-2-ethylhexyl monocarbonate used was changed from 2.50 g to 1.25 g, and the amount of styrene used as the first monomer was changed from 70 g to 75 g, and the amount of butyl acrylate used was changed from 5 g to 0 g. Except for this, the expandable particles, expanded particles, and molded bodies were produced in the same manner as in Example 1.
[0138] Comparative Example 2 In this example, the amount of t-hexyl peroxybenzoate used in producing the composite resin particles in Example 1 was changed from 0.21 g to 0.42 g, and further, the brominated flame retardant was changed from 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane to bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone (FCP-65CN (50% decomposition temperature: 331°C) manufactured by Suzuhiro Chemical Co., Ltd.). Except for this, the expandable particles, expanded particles, and molded bodies were produced in the same manner as in Example 1.
[0139] Comparative Example 3 In this example, the core particles used in Example 1 were changed to core particles prepared by the following procedure, the amount of t-butylperoxy-2-ethylhexyl monocarbonate used was changed from 2.5 g to 2.58 g, the amount of t-hexyl peroxybenzoate used was changed from 0.21 g to 0 g, and the amount of 2,3-dimethyl-2,3-diphenylbutane used as a flame retardant auxiliary was changed from 1.67 g to 0 g. Except for this, expandable particles, expanded particles, and molded bodies were prepared in the same manner as in Example 1.
[0140] [Creation of core particles] As the ethylene-based resin, we prepared a linear low-density polyethylene polymerized using a metallocene polymerization catalyst (Nipolon Z HF210K manufactured by Tosoh Corporation) and an ethylene-vinyl acetate copolymer (EVA) with a vinyl acetate content of 46 mass% (EV45LX manufactured by Dow Mitsui Polychemicals Co., Ltd.). As a dispersion size expander, we prepared an acrylonitrile-styrene copolymer (AS-XGS manufactured by Denka Co., Ltd.). Further, a flame retardant master batch (Nikko Bix Co., Ltd., brominated styrene-butadiene copolymer (Chemtura Corporation, Emerald 3000): 70.03 mass%, TBA-bis (2,3-dibromopropyl ether) (Suzuhiro Chemical Co., Ltd., FCP-680): 12.05 mass%, poly (1,4-diisopropylbenzene) (United Initiator Co., Ltd., CCPIB): 3.50 mass%, cresol novolac type epoxy resin (DIC Corporation, Epicron N-680): 7.21 mass%, and antioxidants (ADEKA CORPORATION, Adeka STAB PEP-36): 0.41 mass% and (Songwon Corporation, Songnox 4425): 6.80 mass%) were prepared. Furthermore, polyethylene wax (Baker Petrolite Co., Ltd., PW1000) was prepared as a lubricant.
[0141] Then, 66.05 kg of LLDPE and 7.33 kg of EVA as ethylene-based resins, 3.62 kg of acrylonitrile-styrene copolymer as a dispersion diameter expander, 18 kg of a flame retardant master batch, and 5 kg of polyethylene wax were added to a Henschel mixer (FM-75E manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) and mixed for 5 minutes. Next, the mixture was melt-kneaded at a barrel temperature of 180° C. using a single-screw extruder (PMS30-28 manufactured by IKG Corporation) with an inner barrel diameter of 30 mm, and cut by a strand cut method to obtain core particles of an average weight of 0.35 mg / piece.
[0142] [Table 1]
[0143] [Table 2]
[0144] As shown in Table 2, the molded articles obtained from the expandable particles of Examples 1 to 5 are lightweight and have excellent flexural modulus and flexural breaking strain. These molded articles also meet the FMVSS No. 302 standard and have excellent flame retardancy even when they have thin-walled parts. Therefore, the molded articles obtained from the expandable particles of Examples 1 to 5 can be suitably used as interior materials for vehicles.
Claims
1. A vehicle interior material made of a foamed bead molding, The foamed bead molding has a base resin that is a composite resin obtained by impregnating and polymerizing an ethylene-based resin with a styrene-based monomer, and contains a flame retardant containing a brominated bisphenol A-based flame retardant as a main component as a brominated bisphenol-based flame retardant, the organic physical blowing agent remains in the expanded bead molding, The content of xylene insoluble matter in the composite resin is 5% by mass or more and 20% by mass or less, The apparent density of the expanded bead molding is 15 kg / m 3 More than 40kg / m 3 is as follows: the expanded bead molding has a breaking strain of 20% or more and a bending modulus of elasticity of 20 MPa or more, as measured in accordance with JIS K 7221-2:2006; The content of a styrene-based monomer in the expanded bead molding is 0 ppm by mass or more and 50 ppm by mass or less, A vehicle interior material that satisfies any one of the following conditions when a flammability test based on FMVSS No. 302 is conducted: (1) the foamed bead molding exhibits self-extinguishing properties; and (2) the burning rate of the foamed bead molding is 60 mm / min or less.
2. 2. The vehicle interior material according to claim 1, wherein (1) the foamed bead molding exhibits self-extinguishing properties when a flammability test based on FMVSS No. 302 is carried out.
3. 3. The vehicle interior material according to claim 1, wherein the amount of the brominated bisphenol-based flame retardant in the expanded bead molding is 1.2 parts by mass or more and 3.0 parts by mass or less per 100 parts by mass of the composite resin.
4. 4. The vehicle interior material according to claim 1, wherein a mass ratio of the component derived from the ethylene-based resin to the component derived from the styrene-based monomer in the composite resin is 20:80 to 5:95 (component derived from the ethylene-based resin:component derived from the styrene-based monomer).
5. The glass transition temperature of the methyl ethyl ketone soluble matter in the composite resin is 105° C. or higher. The vehicle interior material according to any one of claims 1 to 4.
6. The vehicle interior material according to any one of claims 1 to 5, wherein the content of the organic physical blowing agent in the expanded bead molding is 0.1% by mass or more and 3% by mass or less.
Citation Information
Patent Citations
Flame retardant styrene-modified polyethylenic molded foamy
JP1994057027A
Polystyrene-base resin extruded foam plate and method for producing the same
JP2006137862A
Impact absorption member for vehicle
JP2013199600A
Method for producing expandable composite resin particles
JP2016037530A
Expandable composite resin particle
JP2016180038A